Continuity of motivation in higher education: A three-year follow-up study - Müller, Florian H. (Array, 2005)
This study investigates the question how the quality of students’ learning motivation changes within a period of 3 years. Of special interest is which conditions of the learning environment are responsible for the stability or respectively the change of learning motivation. Deci and Ryan’ s (2002) self-determination theory (SDT) provides the theoretical foundation of this paper. It allows a differentiated analysis of the qualities of learning motivation and also suggests that motivational processes are highly influenced by basic psychological needs for autonomy, competence and social relatedness. On three different dates between 2003 and 2005, 104 students of the Faculty of Philosophy in Zadar (Croatia) participated in a questionnaire. Overall, the longitudinal results show that the qualities of learning motivation remain relatively stable. In contrast, particularly the perceived support of autonomy and competence show a significant decline. The evaluation of social relatedness at university, between students and lecturers as well as between groups of students, remains stable on a high level during those three years and appears as a decisive influence on motivation in all of the three assessments. The results are discussed in relation to situational and cultural conditions